2021
DOI: 10.3390/pharmaceutics13030427
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and Pharmacokinectics of Liposomes and Exosomes in a Mouse Model of Sepsis

Abstract: Exosomes have attracted considerable attention as drug delivery vehicles because their biological properties can be utilized for selective delivery of therapeutic cargoes to disease sites. In this context, analysis of the in vivo behaviors of exosomes in a diseased state is required to maximize their therapeutic potential as drug delivery vehicles. In this study, we investigated biodistribution and pharmacokinetics of HEK293T cell-derived exosomes and PEGylated liposomes, their synthetic counterparts, into hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…Whereas this review paper is mainly focused on exosomes, readers can find recent advances regarding other EVs, such as microvesicles, on review papers cited here [12,26]. Focusing on exosome therapeutics, the major tissues distribution of systemically administered exosomes generally include liver, spleen, kidney, lung and gastrointestinal tract, which can be altered by various factors such as cellular origin of exosomes, exosomal membrane composition (e.g., protein, lipid, and glycan) and pathophysiological condition of host [27][28][29][30][31][32][33][34][35]. Exosome engineering for targeted delivery of therapeutic exosomes to various tissues including brain, placenta, heart, spinal cord, and cartilages is also being investigated [36][37][38][39][40][41].…”
Section: Biodistribution and Pharmacokinetics (Pk) Of In Vivo Administered Exosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas this review paper is mainly focused on exosomes, readers can find recent advances regarding other EVs, such as microvesicles, on review papers cited here [12,26]. Focusing on exosome therapeutics, the major tissues distribution of systemically administered exosomes generally include liver, spleen, kidney, lung and gastrointestinal tract, which can be altered by various factors such as cellular origin of exosomes, exosomal membrane composition (e.g., protein, lipid, and glycan) and pathophysiological condition of host [27][28][29][30][31][32][33][34][35]. Exosome engineering for targeted delivery of therapeutic exosomes to various tissues including brain, placenta, heart, spinal cord, and cartilages is also being investigated [36][37][38][39][40][41].…”
Section: Biodistribution and Pharmacokinetics (Pk) Of In Vivo Administered Exosomesmentioning
confidence: 99%
“…They found that substantial number of exosomes were delivered to the lung compared to healthy mouse after intravenous injection, of which more than 30% of exosomes were delivered to the lung in sepsis-induced mouse after 1 h of injection whereas almost none were detected in the lung of healthy mouse. Also, prolonged retention of exosomes in the blood circulation were observed due to liver dysfunction [ 28 ]. In other disease models, clearance of fluorophore labeled exosomes (10 nmol, intravenous) from blood in normal mice were 0.0054–0.0154 mL/min [ 67 ], whereas Gaussia luciferase (gLuc)-lactadherin (LA) labeled exosomes (5 µg, intravenous) in macrophage-depleted mice [ 42 ] and 125 I labeled exosomes (4 × 10 5 cpm, intravenous) in Parkinson’s disease mouse model [ 65 ] were 0.651 ± 0.157 mL/h and 0.016 mL/min, respectively.…”
Section: Factors Modulating Biodistribution and Pk Of In Vivo Administered Exosomesmentioning
confidence: 99%
“…Evidence shows that renal excretion may not contribute to the rapid clearance of EVs from circulation [38]. However, biliary excretion and renal clearance of exosomes have been observed as soon as 5 h after administration [43].…”
Section: Exosome Biogenesis Isolation and Characterizationmentioning
confidence: 99%
“…Exosomes from different cell types have shown an asymmetric biodistribution [42]. Furthermore, the biodistribution and retention of exosomes in a particular tissue can be influenced by pathophysiological processes [43]. In this regard, exosome surface modifications have allowed the attachment of different moieties for targeted drug delivery.…”
Section: Exosome Biogenesis Isolation and Characterizationmentioning
confidence: 99%
“…The abilities of MSC EVs to deliver bioactive macromolecular cargo to recipient cells as well as their more drug-like qualities as compared to whole cell-based therapies make MSC EVs especially attractive for tissue repair and regeneration. However, EVs in general are also characterized by relatively rapid clearance from the blood after systemic delivery [14][15][16],…”
Section: Introductionmentioning
confidence: 99%